Autophagy in the myocardium: Dying for survival? - Goswami, Shyamal K (Pulsus Group Inc, 2006)
Autophagy is an intracellular phenomenon in which a cell digests its own constituents. Autophagy is well conserved in nature from lower eukaryotes to mammals and has been attributed to disparate physiological events – including cell death, the mechanism of which is different from apoptosis. However, unlike in apoptosis, in which a family of cysteine proteases (caspases) and a number of other regulatory proteins have been identified and characterized, the mechanism of autophagic cell death remains unclear. In addition, the general mechanisms by which autophagy is initiated and modulated are just emerging, and several lines of evidence indicate that activated class I phosphatidylinositol 3-kinase and mammalian target of rapamycin (mTOR) inhibit autophagy, while class III phosphatidylinositol 3-kinase acts as a facilitator. Autophagy has been attributed to a number of cardiac disorders, such as ischemic cardiomyopathy, cardiac hypertrophy, hemochromatosis and myocardial aging. Induction of ventricular hypertrophy is associated with decreased autophagy, whereas it is enhanced during the regression of hypertrophy. Induction of acute cardiotoxicity by the anticancer drug anthracycline is also associated with massive cardiomyocyte loss due to autophagy (and apoptosis). Myocyte loss due to autophagy has also been reported during progression from compensated hypertrophy to heart failure in a pressure-overloaded model. Although the depth and dimension of the regulatory network that modulates autophagy in mammalian cells has yet to emerge, existing evidence suggests that it is an integral part of maintaining cellular metabolism, organelle homeostasis and redox equilibrium. Thus, it is a likely possibility that autophagy plays a crucial role in maintaining healthy myocytes in the myocardium.